Efficacy and safety of Centella asiatica (L.) Urb. [Apiaceae] as a dietary supplement for glycemic control and lipid regulation in patients with type 2 diabetes: a randomized controlled trial in Thailand - Tawanwongsri, Weeratian; Mordmuang, Auemphon; Phenwan, Tharin; Siri-archawawat, Doungkamol (Frontiers in Pharmacology, 2025)
PurposeThe objective of this study was to assess the safety and efficacy of Centella asiatica (L.) Urb. [Apiaceae] (CA) as a complementary dietary supplement for glycemic and lipid control in patients with type 2 diabetes mellitus.Patients and methodsA randomized, double-blind, placebo-controlled trial was conducted at Walailak University Hospital, Thailand. Participants were assigned 1:1 to receive C. asiatica (CA) extract 1,200 mg/day or matched placebo for 6 months. The primary outcome was glycated hemoglobin (HbA1c). Secondary outcomes were fasting plasma glucose, low-density lipoprotein cholesterol (LDL-C), and adverse events.ResultsSeventy participants completed the trial (CA n = 34; placebo n = 36). Median age was 57 vs. 60 years, with women comprising 55.9% vs. 41.7% (CA vs. placebo). At 6 months, an unadjusted between-group difference in HbA1c was observed (p = 0.006); however, in the prespecified adjusted analysis (ANCOVA controlling for baseline HbA1c, diabetes duration, and sulfonylurea use) there were no between-group differences in HbA1c, fasting plasma glucose, or LDL-C. Although small within-group reductions in LDL-C were noted, the adjusted between-group comparison was not significant (p = 0.536), so lipid findings are exploratory. CA was well tolerated; mild, transient gastrointestinal symptoms were most common (5/34, 14.7%).ConclusionCA supplementation was safe but did not produce a significant change in glycemic or lipid outcomes compared to placebo. Further studies with larger sample sizes, longer durations, and higher doses are warranted to verify potential metabolic effects.Clinical Trial RegistrationThis trial was registered with the Thai Clinical Trials Registry (TCTR20221219003); https://www.thaiclinicaltrials.org/show/TCTR20221219003.